Nanofiltration for separation and purification of saccharides from biomass - Li, Xianhui (Front Chem Sci Eng, 2021)
Saccharide production is critical to the development of biotechnology in the field of food and biofuel. The extraction of saccharide from biomass-based hydrolysate mixtures has become a trend due to low cost and abundant biomass reserves. Compared to conventional methods of fractionation and recovery of saccharides, nanofiltration (NF) has received considerable attention in recent decades because of its high selectivity and low energy consumption and environmental impact. In this review the advantages and challenges of NF based technology in the separation of saccharides are critically evaluated. Hybrid membrane processes, i.e., combining NF with ultrafiltration, can complement each other to provide an efficient approach for removal of unwanted solutes to obtain higher purity saccharides. However, use of NF membrane separation technology is limited due to irreversible membrane fouling that results in high capital and operating costs. Future development of NF membrane technology should therefore focus on improving material stability, antifouling ability and saccharide targeting selectivity, as well as on engineering aspects such as process optimisation and membrane module design. [Image: see text]